Evaluation of new biomarkers of stress in saliva of sheep. (26th October 2018) - Contreras-Aguilar, M. D.; Escribano, D.; Quiles, A.; López-Arjona, M.; Cerón, J. J.; Martínez-Subiela, S.; Hevia, M. L.; Tecles, F.
Abstract : Some routine handling procedures can produce stress in farm animals, and an adequate control of these stressors is important to avoid the negative effects on animal health and production. The measurement of biomarkers in saliva can be a suitable tool for the evaluation and control of stress. In this report, lipase, butyrylcholinesterase (BChE), total esterase (TEA) and adenosine deaminase (ADA) activities in the saliva of sheep were evaluated as biomarkers of stress. For this purpose, they were measured after inducing stress by facing a dog (experiment 1) and shearing (experiment 2), and comparing them to other stress salivary biomarkers such as α -amylase (sAA) and cortisol, as well as heart rate (HR). Each analyte was measured at the basal time, and during and just after the end of the stressful stimulus, and at various times for the first hour after the period of stress induction. Values were compared with those obtained from a control group. Lipase was the only analyte that showed significant changes between the stress and the control group in both experiments. Although TEA and ADA increased after stress, no significant differences were seen compared with the control group. Lipase was correlated highly with sAA and HR, in experiment 1; and correlated moderately with cortisol and HR in experiment 2. Lipase showed the greatest percentage increase after the stressful stimuli and less overlap with the control group in the two experiments. From the results of this study it can be concluded that lipase, TEA, BChE and ADA are enzymes present in the saliva of sheep and that they can be measured by using simple and fast colorimetric methods. Further studies should be undertaken with regard to the possible application of lipase as a biomarker of stress in sheep.